1995
DOI: 10.2527/1995.7351381x
|View full text |Cite
|
Sign up to set email alerts
|

Performance and nutrient digestibility in weanling pigs as influenced by yeast culture additions to starter diets containing dried whey or one of two fiber sources

Abstract: Three experiments were conducted using crossbred weanling pigs (7.2 to 8.6 kg; 25 to 29 d of age) to determine the effect on performance and nutrient digestibility of .75% yeast culture (YC) additions to starter diets containing whey or one of two fiber sources. An 18% CP corn-soybean meal basal diet was used in all experiments. In Exp. 1 (n = 192), the addition of YC did not affect ADG, ADFI, or gain: feed ratios (G:F) of pigs fed diets without or with 15% dried whey in two 5-wk trials. In Exp. 2 (n = 174), A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
47
1
5

Year Published

2006
2006
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(62 citation statements)
references
References 16 publications
5
47
1
5
Order By: Relevance
“…They have been reported to produce a variety of beneficial production responses in animals. However, other studies have reported the no effect from live yeast supplementation (Kornegay et al 1995). The yeast cell wall components, especially mannan oligosaccharides (MOS), are capable of adsorbing enteropathogens.…”
Section: Introductionmentioning
confidence: 96%
“…They have been reported to produce a variety of beneficial production responses in animals. However, other studies have reported the no effect from live yeast supplementation (Kornegay et al 1995). The yeast cell wall components, especially mannan oligosaccharides (MOS), are capable of adsorbing enteropathogens.…”
Section: Introductionmentioning
confidence: 96%
“…Yeasts are the group of microorganisms to have been the most exploited commercially. Incorporated alive as probiotics into the feed of weanling pigs, yeasts can stimulate digestion, be a source of interesting enzymes (phytases), and help to maintain the microbial balance in the intestine of these animals [6][7][8][9]. Dead yeasts can be used also as prebiotics having a non-negligible effect on animal health [providing mannan oligosaccharides (MOS), for instance] [10].…”
Section: Introductionmentioning
confidence: 99%
“…It can be speculated if these differences can be attributed to differences in origin and dietary level of nucleotides, to variations in the adaptation period of the administered nucleotides before the start of the experiment and/or to differences in the age of the experimental animals. For example, in a study by Kornegay et al (83) with piglets (aged 25-29 d) there was no effect on apparent digestibilities of DM, N, neutral-detergent fibre and aciddetergent fibre, as well as on P, when 0·75 % of a commercial product containing nucleotides was fed. Similarly, N Sauer, M Eklund, S Roth and R Mosethin (unpublished results) found no effects on ileal digestibilities of DM, crude protein, crude ash and crude fibre in piglets (aged 24 -38 d) fed a diet supplemented with 1000 parts per million of a commercial product containing nucleotides.…”
Section: Biological Effects Of Dietary Nucleotidesmentioning
confidence: 99%
“…In several studies dietary nucleotides as a yeast product were added to the diets of pigs of different ages but failed to improve growth performance (4,11,53,55,83,86,96,116,117) . Similarly, a study by Sijben et al (118) showed that dietary yeast nucleotides (Saccharomyces cerevisiae) did not affect energy intake, heat production and energy retention of barrows.…”
Section: Zootechnical Effectsmentioning
confidence: 99%